Age of First Arrhythmic Event in Brugada Syndrome: Data From the SABRUS (Survey on Arrhythmic Events in Brugada Syndrome) in 678 Patients. (December 2017) - Milman, Anat; Andorin, Antoine; Gourraud, Jean-Baptiste; Sacher, Frederic; Mabo, Philippe; Kim, Sung-Hwan; Maeda, Shingo; Takahashi, Yoshihide; Kamakura, Tsukasa; Aiba, Takeshi; Conte, Giulio; Juang, Jimmy J.M.; et al.
Abstract : Background: Data on the age at first arrhythmic event (AE) in Brugada syndrome are from limited patient cohorts. The aim of this study is 2-fold: (1) to define the age at first AE in a large cohort of patients with Brugada syndrome, and (2) to assess the influence of the mode of AE documentation, sex, and ethnicity on the age at first AE. Methods and Results: A survey of 23 centers from 10 Western and 4 Asian countries gathered data from 678 patients with Brugada syndrome (91.3% men) with first AE documented at time of aborted cardiac arrest (group A, n=426) or after prophylactic implantable cardioverter–defibrillator implantation (group B, n=252). The vast majority (94.2%) of the patients were 16 to 70 years old at the time of AE, whereas pediatric (<16 years) and elderly patients (>70 years) comprised 4.3% and 1.5%, respectively. Peak AE rate occurred between 38 and 48 years (mean, 41.9±14.8; range, 0.27–84 years). Group A patients were younger than in Group B by a mean of 6.7 years (46.1±13.2 versus 39.4±15.0 years; P <0.001). In adult patients (≥16 years), women experienced AE 6.5 years later than men ( P =0.003). Whites and Asians exhibited their AE at the same median age (43 years). Conclusions: SABRUS (Survey on Arrhythmic Events in Brugada Syndrome) presents the first analysis on the age distribution of AE in Brugada syndrome, suggesting 2 age cutoffs (16 and 70 years) that might be important for decision-making. It also allows gaining insights on the influence of mode of arrhythmia documentation, patient sex, and ethnic origin on the age at AE. Abstract : Supplemental Digital Content is available in the text.